"Which hat do I say I'm wearing?": identity work of independent coaching practitioners. Issue 8 (27th August 2014) - Evans, Christina; Lines, David
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to provide an insight into the complexities of the identity work performed by independent coaches, based on an investigation into their "lived experiences". The emerging coaching industry has created opportunities for individuals wishing to pursue a career as independent executive/career coaches. Design/methodology/approach – This exploratory investigation was conducted using the principles of grounded theory, drawing on insights from "knowledgeable informants" (18 in total) gained through interviews and focus group discussion. Findings – Despite the attractiveness of pursuing an independent career, the findings surfaced a number of tensions in the way that independent coaches transform and perform their identity. One tension involves balancing notions of self-identity and "ideal work" with presenting a credible self to different client groups, the purchasers of their services. Research limitations/implications – As the research focused on a specific category of independent practitioners, more research is required to assess the generalizability of the findings to other categories of practitioners. Practical implications – A framework illuminating the processual nature of identity work among independent coaches is presented. This could be used to inform developmental conversations with aspiring independent coaches, or to support the content on formal coaching programmes. Originality/value – In drawing attention to the complexities of identity work performed by independent coaches, given the contingencies affecting their work, this research offers a different contribution to the coaching literature.